CHALLENGES IN ESTONIAN RESEARCH POLICY: A BIBLIOMETRIC PERSPECTIVE. - Hirv, Tanel (TRAMES: A Journal of the Humanities & Social Sciences, 2025)
Over the past three decades, the Estonian research landscape has evolved from modest beginnings to international recognition. Accession to the European Union, foreign funding, and international collaboration have been key drivers of this progress. However, upon closer inspection, many celebrated scientific achievements have proven to be overstated or methodologically questionable. This article analyses Estonia's scientific development using publication and citation metrics, authorship patterns, and demographic data. It highlights the limitations of citation-based benchmarks for evaluating national research and questions the relevance of bibliometric percentile targets in science policy. The study also challenges the notion that declining PhD graduation rates are primarily due to demographic changes, pointing instead to structural factors. The findings of the study highlight the need to reassess the role of bibliometric indicators in research policy and performance evaluation.